(untitled) (Південний архів (історичні науки), 2023)
Purpose. The aim of the research is to reveal the tasks and goals set by the Communist Party for trade and economic education in the 1920s of the twentieth century on the example of the Odessa Institute of National Economy. Methods. Methodology is based on the principles of historicism, systematization, scientificity, verification, authorial objectivity, moderate constructivism, as well as the use of general scientific (analysis, synthesis, generalization) and special-historical (historical-systemic, historical-typological) methods. Results. The article presents the main organizational aspects of the Odessa Institute of National Economy, reveals the tasks and goals set by the authorities for scientific and pedagogical activities of the institute, also focuses on the social composition of students and their education at trade and cooperative faculties. It should be emphasized that this topic is relevant, as in Ukraine there are only fragmentary studies on trade and economic education in the 1920s. Conclusions. The article presents archival documents that provide data on the financial support of the institute, the role of cooperative organizations in the financial assistance of the cooperative faculty of the Institute. The paper emphasizes the lack of commercial specialists and the difficult financial situation of students at that time. Attention is paid to problems related to funding and enrollment of students in the cooperative faculty. The authors emphasize the role of trade and economic education in the birth of a new commercial and proletarian intelligentsia. On the basis of archival documents, we can trace the history of the institutions of the national economy, and most importantly comment on the main goals of the government to create a new base of trade and economic education and new specialists in the field of trade. From these conclusions we can say that trade and economic education occupied a leading position in the socialist construction of the time, and most importantly had to play the role of “cog” in the birth of a new philosophy of trade and economics.